Preparation method of screw

By optimizing material selection and selection laser melting technology, combining thermal isostatic pressure and comprehensive heat treatment process, and finally using high-performance coating materials for thermal spraying, the problem of insufficient strength and toughness of existing screw materials in extreme environments is solved. Higher strength, toughness and corrosion resistance are achieved.

CN119457115APending Publication Date: 2025-02-18JIAXING FUERTE MACHINERY MFG CO LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411180611.9
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-08-27
Publication Date
2025-02-18

AI Technical Summary

Technical Problem

The existing screw materials used to connect wind wheel blades and hubs are insufficient in extreme environments and are difficult to withstand huge wind and dynamic loads. At the same time, traditional processing methods are difficult to ensure high accuracy and consistency.

Method used

By optimizing material selection, high-purity alloy powder is used and additive manufacturing is performed using selective laser melting (SLM) technology, combining thermal isostatic pressure and comprehensive heat treatment processes including quenching, tempering and finishing, and finally high-performance coating The layer material is thermally sprayed.

Benefits of technology

It significantly improves the strength and toughness of the screw, can better withstand the huge forces generated by the wind wheel blades, ensures the stability and safety of the connection parts, and improves corrosion resistance and extends the service life.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119457115A_ABST
    Figure CN119457115A_ABST
Patent Text Reader

Abstract

The invention relates to a preparation process of a screw rod, in particular to a preparation method of the screw rod, which comprises the following steps: preparing alloy powder; the alloy powder is subjected to additive manufacturing through the selective laser melting (SLM) technology, and a screw blank is formed; the screw rod blank obtained after additive manufacturing is directly subjected to pre-sintering treatment; the screw rod blank is put into a hot isostatic pressing furnace to be treated and then cooled, an alloy bar is obtained, turning and milling are conducted on the alloy bar, a screw rod blank is machined, and electroplating treatment is conducted on the surface of the screw rod blank; carrying out quenching and tempering treatment on the electroplated screw rod blank; carrying out finish machining on the heat-treated screw rod blank, and carrying out thread machining on the screw rod by adopting a precision turning or rolling process; according to the method, material selection and the selective laser melting (SLM) technology are optimized, so that the screw has higher strength and toughness and can better bear huge force generated by a wind wheel blade, and the stability and safety of a connecting part are ensured.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to a preparation process of a screw rod, and more specifically, to a preparation method of a screw rod. Background Art

[0002] As the global demand for renewable energy increases, wind power generation has been widely used as a clean and efficient form of energy. The key components of a wind turbine include wind rotor blades, hubs, main shafts, gearboxes, towers and bases. Among them, the connection between the wind rotor blades and the hub plays a vital role in the entire system. This connection needs to withstand huge wind loads, dynamic loads and environmental corrosion, so the performance requirements for its connecting screw are extremely demanding.

[0003] The low-carbon steel and stainless steel materials currently used for connection screws do not have sufficient strength and toughness in extreme environments and are unable to withstand huge wind loads and dynamic loads. In addition, traditional machining methods make it difficult to ensure the high precision and consistency of each screw, and dimensional deviations are prone to occur. Summary of the invention

[0004] In view of the shortcomings of the prior art, the purpose of the present invention is to provide a preparation method that optimizes material selection and additive manufacturing technology to make the screw have higher strength and toughness and be able to withstand the huge force generated by the wind wheel blades under high-speed rotation and strong wind loads.

[0005] To achieve the above object, the present invention provides the following technical solutions: A method for preparing a screw, comprising the following steps: S1. Prepare alloy powder; S2, additively manufacturing the alloy powder using the selective laser melting (SLM) technology to form a screw blank; S3, directly pre-sintering the screw blank after additive manufacturing; S4, placing the pre-sintered screw blank into a hot isostatic pressing furnace for treatment and then cooling to obtain an alloy rod; S5, turning and milling the taken-out alloy bar material to form a screw blank, thereby forming a basic shape of the screw and a preliminary thread profile; S6. Electroplating the surface of the screw blank; S7, quenching and tempering the electroplated screw blank; S8, finishing the screw blank after heat treatment, including outer cylindrical grinding, inner hole grinding and end face grinding to obtain the screw, S9, use precision turning or rolling technology to process multiple screws for thread processing; S10. Coating the screw after thread processing.

[0006] The present invention is further configured as follows: the alloy components in step S1 are calculated by weight as follows: iron (Fe) 50-60%, chromium (Cr) 15-20%, nickel (Ni) 10-15%, molybdenum (Mo) 5-10%, carbon (C) 0.5-1%, silicon (Si) 0.5-1%, manganese (Mn) 0.5-1%, and vanadium (V) 0.1-0.5%.

[0007] The present invention is further configured as follows: the step S1 further includes pre-treating the alloy powder: specifically, drying the alloy powder at 120°C-150°C for 3-6 hours to ensure that the moisture of the powder is less than 0.1%, and mixing the powder using a high-energy ball mill at a speed of 300 rpm, a time of 4 hours, and a ball-to-material ratio of 10:1. The anti-oxidation film is coated on the surface of the alloy powder using chemical vapor deposition (CVD) technology. The processing gas is methane or ethane, the processing temperature is 500°C, and the time is 1 hour. The alloy powder was surface treated by plasma activation technology, with a plasma power of 100 W and a treatment time of 30 minutes.

[0008] The present invention is further configured as follows: the specific steps in step S2 are: S2.1. Spread the pretreated alloy powder evenly on the building platform with a powder layer thickness of 0.03 mm. S2.2, using a computer to control the laser beam to selectively melt the powder according to the preset three-dimensional model graphics, the laser power is set to 400W, and the scanning speed is 1200mm / s; S2.3, after the laser beam scanning is completed, the platform descends one layer of thickness, and steps S2.1 and S2.2 are repeated to melt the powder layer by layer and solidify it until the entire screw blank is constructed; S2.4. After the build is complete, remove the screw blank from the build platform and perform a preliminary cleanup to remove excess powder.

[0009] The present invention is further configured as follows: the pre-sintering steps of step S3 are as follows: S3.1. Place the screw blank into a pre-sintering furnace; S3.2, gradually increase the temperature of the pre-sintering furnace to 600°C-700°C, heating at a heating rate of 10°C per minute; S3.3. After reaching the target temperature, maintain the constant temperature for 1-2 hours to promote bonding between powder particles; S3.4. After pre-sintering is completed, slowly cool down to room temperature and take the screw blank out of the pre-sintering furnace.

[0010] The present invention is further configured as follows: Step S4 specifically includes: S4.1. Place the pre-sintered screw blank into a container and ensure that there are no impurities and oxygen in the container; S4.2, placing the container in a hot isostatic pressing furnace; S4.3, gradually raise the temperature to 900°C-1000°C at a heating rate of 5-10°C per minute; S4.4, increase the pressure to 180-220MPa and maintain constant temperature and pressure for 5-8 hours; S4.5. While maintaining the temperature and pressure, slowly cool down by controlling the cooling rate to ensure that the internal stress of the screw blank is evenly released; S4.6, after cooling to room temperature, reduce the pressure to normal pressure; S4.7. Take the treated alloy bars out of the hot isostatic pressing furnace and conduct preliminary inspection.

[0011] The present invention is further configured as follows: Step S7 specifically includes: S7.1. Quench the electroplated screw blank at a temperature of 800-900°C and keep the temperature constant so that the screw is evenly heated at this temperature for 3-5 hours. Then the screw is immersed in the cooling medium for rapid cooling; S7.2. The quenched screw is tempered. The quenched screw blank is tempered, the temperature is kept constant for 1-2 hours, and then slowly cooled to room temperature.

[0012] The present invention is further configured as follows: Step S10 specifically includes: S10.1, Surface pretreatment: ultrasonic cleaning of the screw, roughening of the screw surface by sandblasting or shot blasting to ensure that the surface roughness is between 50-100 microns; S10.2. Cobalt-based alloy is used and thermal spraying is performed using high-velocity oxygen-fuel spraying (HVOF) equipment. During the process, the screw is fixed on a rotating device and kept rotating evenly to ensure that the coating evenly covers the entire screw surface. The coating is sprayed layer by layer according to the set spraying parameters until the required coating thickness is reached. The coating thickness is 0.1-0.3mm.

[0013] S10.3. After thermal spraying, the screw is naturally cooled to room temperature, and then tempered. The tempering temperature is set to 200-300°C for 1-2 hours, and finally cooled to room temperature.

[0014] Compared with the shortcomings of the prior art, the beneficial effects of the present invention are: By optimizing material selection (using high-purity alloy powder) and selective laser melting (SLM) technology, the screw has higher strength and toughness, can better withstand the huge force generated by the wind rotor blades, and ensure the stability and safety of the connection.

[0015] The use of high-performance coating materials significantly improves the corrosion resistance of the screw, giving it a longer service life in marine and coastal environments. BRIEF DESCRIPTION OF THE DRAWINGS

[0016] Figure 1 It is a process flow chart of the present invention. DETAILED DESCRIPTION

[0017] Reference Figure 1 Embodiment 1 of the present invention is further described.

[0018] Step 1: Prepare alloy powder; the alloy composition by weight is: iron (Fe) 50-60%, chromium (Cr) 15-20%, nickel (Ni) 10-15%, molybdenum (Mo) 5-10%, carbon (C) 0.5-1%, silicon (Si) 0.5-1%, manganese (Mn) 0.5-1%, vanadium (V) 0.1-0.5%. The materials used in this application and subsequent process production are specifically selected as follows: Iron (Fe) 55%, chromium (Cr) 20%, nickel (Ni) 12%, molybdenum (Mo) 10%, carbon (C) 1%, silicon (Si) 1%, manganese (Mn) 0.5%, and vanadium (V) 0.5%.

[0019] The alloy powder is dried at 120℃-150℃ for 3-6 hours to ensure that the moisture of the powder is less than 0.1%. The powder is mixed in a high-energy ball mill at a speed of 300rpm for 4 hours and a ball-to-powder ratio of 10:1. The anti-oxidation film is coated on the surface of the alloy powder using chemical vapor deposition (CVD) technology. The processing gas is methane or ethane, the processing temperature is 500°C, and the time is 1 hour. The alloy powder was surface treated by plasma activation technology, with a plasma power of 100 W and a treatment time of 30 minutes.

[0020] The second step, S2.1, uses the selective laser melting (SLM) technology to perform additive manufacturing on the alloy powder to form a screw blank, specifically: the pre-treated alloy powder is evenly spread on the building platform, and the powder layer thickness is 0.03 mm; S2.2 uses a computer-controlled laser beam to selectively melt the powder according to the preset three-dimensional model graphics. The laser power is set to 400W and the scanning speed is 1200mm / s; After the laser beam scanning is completed, the platform descends one layer of thickness and repeats steps S2.1 and S2.2 to melt and solidify the powder layer by layer until the construction of the entire screw blank is completed.

[0021] After the build is complete, the screw blank is removed from the build platform and an initial cleanup is performed to remove excess powder.

[0022] The third step is to place the screw blank into the pre-sintering furnace; gradually increase the temperature of the pre-sintering furnace to 600℃-700℃, and heat at a heating rate of 10℃ per minute; after reaching the target temperature, maintain a constant temperature for 1-2 hours to promote the bonding between the powder particles; after the pre-sintering is completed, slowly cool down to room temperature and take the screw blank out of the pre-sintering furnace.

[0023] Step 4: Load the pre-sintered screw blank into a container and ensure that there are no impurities and oxygen in the container; place the container in a hot isostatic pressing furnace; gradually increase the temperature to 900℃-1000℃, and heat at a heating rate of 5-10℃ per minute; increase the pressure to 180-220MPa, and maintain a constant temperature and pressure state for 5-8 hours; while maintaining the temperature and pressure, slowly cool down by controlling the cooling rate to ensure that the internal stress of the screw blank is evenly released; after cooling to room temperature, reduce the pressure to normal pressure; take the treated alloy rod out of the hot isostatic pressing furnace and conduct a preliminary inspection.

[0024] Step 5: Turn and mill the alloy bar material to form a screw blank, forming the basic shape of the screw and a preliminary thread profile; Step 6: Electroplating the surface of the screw blank; Step 7: Quench the electroplated screw blank at a temperature of 800°C-900°C and keep the temperature constant so that the screw blank is evenly heated at this temperature for 3-5 hours, and then immerse the screw blank in a cooling medium for rapid cooling; The quenched screw is tempered, the quenched screw blank is tempered, the temperature is kept constant for 1-2 hours, and then slowly cooled to room temperature.

[0025] Step 8: Finish the heat-treated screw blank by grinding the outer circle, inner hole and end surface to obtain the screw. Step 9: Use precision turning or rolling technology to process multiple screws for thread processing; Step 10. Surface pretreatment: ultrasonically clean the screw and roughen the screw surface by sandblasting or shot blasting to ensure that the surface roughness is between 50-100 microns; Cobalt-based alloy is used, and high-speed oxygen fuel spray (HVOF) equipment is used for thermal spraying. During the process, the screw is fixed on a rotating device and kept rotating evenly to ensure that the coating evenly covers the entire screw surface. The operation is carried out according to the set spraying parameters, and the coating is sprayed layer by layer until the required coating thickness is reached. The coating thickness is 0.1-0.3mm. After the thermal spraying is completed, the screw is naturally cooled to room temperature, and then tempered. The tempering temperature is set to 200-300℃, the time is 1-2 hours, and finally cooled to room temperature.

[0026] Comparative case 1: The steps of replacing the second step by the traditional process, that is, generating the billet screw from the alloy powder, are as follows: The prepared alloy powder is placed in a mold and pressed into a blank with a screw shape by a hot pressing process. The powder is pressed and formed by high pressure at high temperature, usually using a pressure of 500-700MPa and a temperature of 800-1000℃. The pressed screw blank is placed in a sintering furnace for sintering treatment to enhance its mechanical strength and density, wherein the sintering temperature is 1200℃-1400℃ and the sintering time is 2-4 hours.

[0027] Comparative case 2: The tenth step of coating the screw after thread machining is not taken.

[0028] Comparative case 3: In the first step, the alloy powder is not dried, mixed, or coated with an anti-oxidation film. Plasma activation treatment.

[0029] Based on the above comparison, the following test table shows:

[0030] Based on tensile strength: The tensile strength of the embodiment of the present application is the highest, indicating that the SLM technology and comprehensive heat treatment process significantly improve the density and mechanical properties of the material. Removing the coating treatment and alloy powder pretreatment will reduce the tensile strength, but the impact is small; using traditional machining instead of SLM technology has the greatest impact on tensile strength.

[0031] Based on hardness: The hardness of the embodiment of the present application is the highest, indicating that the SLM technology and comprehensive heat treatment process effectively improve the hardness of the material. The lack of coating treatment has a certain impact on the hardness, while the lack of alloy powder pretreatment has a greater impact.

[0032] Based on corrosion resistance: The corrosion resistance of the embodiment of the present application is the best, indicating that comprehensive electroplating and thermal spraying treatments significantly improve the corrosion resistance of the screw. Decoating treatment has the greatest impact, while traditional machining and lack of alloy powder pretreatment also lead to a decrease in corrosion resistance.

[0033] Based on residual stress: The residual stress of the embodiment of the application is the smallest, indicating that the comprehensive heat treatment process effectively reduces the residual stress inside the screw. The lack of alloy powder pretreatment leads to the largest residual stress, while traditional machining and lack of coating treatment also increase the residual stress.

[0034] The above description is only a preferred embodiment of the present invention and is not intended to limit the present invention. Common changes and substitutions made by those skilled in the art within the scope of the technical solution of the present invention should be included in the protection scope of the present invention.

Claims

1. A method for preparing a screw, characterized in that: The steps include: S1. Prepare alloy powder; S2, additively manufacturing the alloy powder using the selective laser melting (SLM) technology to form a screw blank; S3, directly pre-sintering the screw blank after additive manufacturing; S4, placing the pre-sintered screw blank into a hot isostatic pressing furnace for treatment and then cooling to obtain an alloy rod; S5, turning and milling the taken-out alloy bar material to form a screw blank, thereby forming a basic shape of the screw and a preliminary thread profile; S6. Electroplating the surface of the screw blank; S7, quenching and tempering the electroplated screw blank; S8, finishing the heat-treated screw blank, including outer cylindrical grinding, inner hole grinding and end face grinding to obtain the screw, S9, thread the screw using precision turning or rolling technology; S10. Coating the screw after thread processing.

2. The method for preparing a screw according to claim 1, characterized in that: The alloy components in step S1 are calculated by weight as follows: iron (Fe) 50-60%, chromium (Cr) 15-20%, nickel (Ni) 10-15%, molybdenum (Mo) 5-10%, carbon (C) 0.5-1%, silicon (Si) 0.5-1%, manganese (Mn) 0.5-1%, and vanadium (V) 0.1-0.5%.

3. The method for preparing a screw according to claim 2, characterized in that: Said Step S1 also includes pre-treating the alloy powder: specifically, drying the powder at 120°C-150°C for 3-6 hours to ensure that the moisture of the powder is less than 0.1%, and mixing the powder using a high-energy ball mill at a speed of 300 rpm for 4 hours and a ball-to-material ratio of 10:

1. The anti-oxidation film is coated on the surface of the alloy powder using chemical vapor deposition (CVD) technology. The processing gas is methane or ethane, the processing temperature is 500°C, and the time is 1 hour. The alloy powder was surface treated by plasma activation technology, with a plasma power of 100 W and a treatment time of 30 minutes.

4. The method for preparing a screw according to claim 2, characterized in that: The specific steps in step S2 are: S2.

1. Spread the pretreated alloy powder evenly on the building platform with a powder layer thickness of 0.03 mm. S2.2, using a computer to control the laser beam to selectively melt the powder according to the preset three-dimensional model graphics, the laser power is set to 400W, and the scanning speed is 1200mm / s; S2.3, after the laser beam scanning is completed, the platform descends one layer of thickness, and steps S2.1 and S2.2 are repeated to melt the powder layer by layer and solidify it until the entire screw blank is constructed; S2.

4. After the build is complete, remove the screw blank from the build platform and perform a preliminary cleanup to remove excess powder.

5. The method for preparing a screw according to claim 3, characterized in that: The steps of pre-sintering in step S3 are as follows: S3.

1. Place the screw blank into a pre-sintering furnace; S3.2, gradually increase the temperature of the pre-sintering furnace to 600°C-700°C, heating at a heating rate of 10°C per minute; S3.

3. After reaching the target temperature, maintain the constant temperature for 1-2 hours to promote bonding between powder particles; S3.

4. After pre-sintering is completed, slowly cool down to room temperature and take the screw blank out of the pre-sintering furnace.

6. The method for preparing a screw according to claim 2, characterized in that: The step S4 specifically includes: S4.

1. Place the pre-sintered screw blank into a container and ensure that there are no impurities and oxygen in the container; S4.2, placing the container in a hot isostatic pressing furnace; S4.3, gradually raise the temperature to 900°C-1000°C at a heating rate of 5-10°C per minute; S4.4, increase the pressure to 180-220MPa and maintain constant temperature and pressure for 5-8 hours; S4.

5. While maintaining the temperature and pressure, slowly cool down by controlling the cooling rate to ensure that the internal stress of the screw blank is evenly released; S4.6, after cooling to room temperature, reduce the pressure to normal pressure; S4.

7. Take the treated alloy bars out of the hot isostatic pressing furnace and conduct preliminary inspection.

7. A method for preparing a screw according to claim 6, characterized in that: The step S7 specifically includes: S7.

1. Quench the electroplated screw blank at a temperature of 800-900°C and keep the temperature constant so that the screw is evenly heated at this temperature for 3-5 hours. Then the screw is immersed in the cooling medium for rapid cooling; S7.2, the quenched screw is tempered, the quenched screw blank is tempered, the temperature range is set to 500℃-600℃, the constant temperature is maintained for 1-2 hours, and slowly cooled to room temperature.

8. The method for preparing a screw according to claim 2, characterized in that: The step S10 specifically includes: S10.1, Surface pretreatment: ultrasonic cleaning of the screw, roughening of the screw surface by sandblasting or shot blasting to ensure that the surface roughness is between 50-100 microns; S10.

2. Cobalt-based alloy is used and thermal spraying is performed using high-velocity oxygen fuel spray (HVOF) equipment. During the process, the screw is fixed on a rotating device and rotated evenly to ensure that the coating evenly covers the entire screw surface. The coating is sprayed layer by layer according to the set spraying parameters until the required coating thickness is reached. The coating thickness is 0.1-0.3mm; S10.

3. After thermal spraying, the screw is naturally cooled to room temperature, and then tempered. The tempering temperature is set to 200-300°C for 1-2 hours, and finally cooled to room temperature.